ANALISIS CAMPURAN KERJA (JMD) DARI RANCANGAN CAMPURAN ASPAL AC-WC PADA REKONSTRUKSI RUAS JALAN TANIWEL SALEMAN - Lakam Laitupa; Vera.Th.C. Siahaya; David D.M. Huwae (Jurusan Teknik Sipil, 2022)
As explained earlier that JMD is required in a process of certifying the feasibility of certain asphalt works, this is influenced by the quality of the asphalt. In the Taniwel-Saleman asphalt preservation work, strong asphalt is needed so that it is resistant to weather and vehicles that pass through it, durability and the price set to create the mixture, as well as to evaluate the Marshall properties of the AC-WC Asphalt Mixture implemented, and to determine the suitability of the marshall properties. AC-WC mixture based on the 2018 Bina Marga specifications. The analysis method uses the AASHTO method and the Bina Marga method. Where the AASHTO method is used to calculate the Hot Mix Design of Marshall manufacture and the Highways method is used to determine the suitability of Marshall properties. From the characteristic values generated in the Marshall test according to the new specifications and from the analysis results, the characteristic values that meet the requirements for VMA, VFA, VIM, Stability Test, flow MQ, then determined the optimum asphalt content of 6.0%. From the test evaluation results that all Marshall characteristics, both in the combined gradation in the laboratory and the combined gradation in the Hot Bin AMP, not all of them meet the requirements according to the AC-WC specification which only meets the optimum asphalt content for the combined gradation in the Hot Bin AMP.Keywords: Asphalt (AC – WC), Marshall Test